2003
DOI: 10.1093/geront/43.3.360
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Family Caregiver Medication Administration Hassles Scale

Abstract: Caregiver medication administration hassles represent a complex, multidimensional construct that warrants consideration in studies of contemporary family caregiver stress, strain, and burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 15 publications
0
54
0
Order By: Relevance
“…While general studies of medication management by family caregivers of older adults are available (Travis, Bethea & Winn 2000;Smith et al 2003;Travis et al 2003;Francis, Smith, Gray & Denham 2006), few studies have focused exclusively on family caregivers of people living with dementia (Cotrell et al 2006, Kaasalainen et al 2011, While et al 2012. In particular, studies of the medication management experience of ethnic minority family …”
Section: Introductionmentioning
confidence: 99%
“…While general studies of medication management by family caregivers of older adults are available (Travis, Bethea & Winn 2000;Smith et al 2003;Travis et al 2003;Francis, Smith, Gray & Denham 2006), few studies have focused exclusively on family caregivers of people living with dementia (Cotrell et al 2006, Kaasalainen et al 2011, While et al 2012. In particular, studies of the medication management experience of ethnic minority family …”
Section: Introductionmentioning
confidence: 99%
“…Studies of caregiver difficulty with medication administration and coordination showed that race and higher education, were associated with higher levels of difficulty. 20,21 Studies of caregivers to cancer patients suggested that the level of patient dependency was the most significant predictor of caregiver difficulty with any type of task. 14,18 Other disease-specific studies have shown factors such as family coping skills 18 and a caregiver's belief in their ability to control outcomes (e.g., self-efficacy) 16 were inversely correlated with caregiver-reported overall task difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…While others have noted the contributions that medication management makes to perceived stress among family caregivers, measurement of this multidimensional stressor was largely absent in the caregiving literature until the recent development of the Family Caregiver Medication Administration Hassles Scale (FCMAHS) (3) . The purpose of this paper is to report a set of variables that are associated with the intensity of medication administration hassles on the FCMAHS that are experienced by family caregivers who manage some or all aspects of the medication regimens for their care recipients over the long-term.…”
Section: Introductionmentioning
confidence: 99%
“…The FCMAHS is a multidimensional measure of the daily irritants associated with managing some or all aspects of another person's medication regimen (3) . The instrument consists of 24 items and four subscales: Information Seeking/Information Sharing (9 items, α = .92), Safety Issues (5 items, α = .83), Scheduling Logistics (7 items, α = .90) and Polypharmacy (3 items, α = .80).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation